Intra-cyclic phases of arm-leg movement and index of coordination in relation to sprint breaststroke swimming in young swimmers - Strzala, M.; Krezalek, P.; Glab, G.; Kaca, M.; Ostrowski, A.; Stanula, A.; Tyka, A. K. (Journal of Sports Science & Medicine, 2013)
Despite the limitations set by FINA regulations, execution technique in breaststroke swimming is being improved thanks to more and more advanced analyses of the efficiency of the swimmer's movements. The aim of this study was to detect the parameters of the time structure of the cycle correlated with the maximal swimming speed at the of 50 meters distance, in order to focus to specific technical aspects in the breaststroke training. In the group of 23 participants, between the age of 15.0 ± 1.17, the breaststroke cycle movement of the arms and legs was divided into two phases: propulsive or non-propulsive. In addition, indices characterizing the temporal coordination of movements of the upper limbs in relation to the lower limbs were distinguished: 1) Arm-Leg Lag - determines the interval between the phases of propulsion generated by upper and lower limbs; 2) Glide or Overlap - the inter-cyclic glide or overlap of the propulsive movement of the upper on lower limbs. Significant dependence was noted between the swim speed (V50surface breast) and the percentage of time of the arm propulsive in-sweep phase 0.64, p < 0.01. A significant correlation was observed between the V50surface breast with the percentage of partially surfaced hand phase of arm recovery 0.54, p < 0.01. Correlation between total leg propulsion and non-propulsion phases with V50surface breast was 0.49 and -0.49 respectively, both p < 0.01. The Glide or Overlap index was significantly related to the swimming speed V50surface breast 0.48, p < 0.05. This type of analysis suggests how to refine the swimming technique, with the goal to improve the current speed capabilities; furthermore the results also indicate the direction of its development in the future swimmers of the group studied.